Sodium Channel Gene Mutations in Children with GEFS+ and Dravet Syndrome: A Cross Sectional Study - TONEKABONI, Seyed Hassan; EBRAHIMI, Ahmad; BAKHSHANDEH BALI, MohammadKazem; HOUSHMAND, Massoud; MOGHADDASI, Mehdi; TAGHDIRI, Mohammad Mahdi; NASEHI, Mohammad Mahdi (Iranian Journal of Child Neurology, 2013)
How to Cite This Article: Tonekaboni SH, Ebrahimi A, Bakhshandeh Bali MK, Houshmand M, Moghaddasi M, Taghdiri MM, Nasehi MM. Sodium Channel Gene Mutations in Children with GEFS+ and Dravet Syndrome: A Cross Sectional Study. Iran J Child Neurol. 2013 Winter; 7 (1):25-29. Objective Dravet syndrome or severe myoclonic epilepsy of infancy (SMEI) is a baleful epileptic encephalopathy that begins in the first year of life. This syndrome specified by febrile seizures followed by intractable epilepsy, disturbed psychomotor development, and ataxia. Clinical similarities between Dravet syndrome and generalized epilepsy with febrile seizure plus (GEFS+) includes occurrence of febrile seizures and joint molecular genetic etiology. Shared features of these two diseases support the idea that these two disorders represent a severity spectrum of the same illness. Nowadays, more than 60 heterozygous pattern SCN1A mutations, which many are de novo mutations, have been detected in Dravet syndrome. Materials & Methods From May 2008 to August 2012, 35 patients who referred to Pediatric Neurology Clinic of Mofid Children Hospital in Tehran were enrolled in this study. Entrance criterion of this study was having equal or more than four criteria for Dravet syndrome. We compared clinical features and genetic findings of the patients diagnosed as Dravet syndrome or GEFS+. Results 35 patients (15 girls and 20 boys) underwent genetic testing. Mean age of them was 7.7 years (a range of 13 months to 15 years). Three criteria that were best evident in SCN1A mutation positive patients are as follows: Normal development before the onset of seizures, onset of seizure before age of one year, and psychomotor retardation after onset of seizures. Our genetic testing showed that 1 of 3 (33.3%) patients with clinical Dravet syndrome and 3 of 20 (15%) patients that diagnosed as GEFS+, had SCN1A mutation. Conclusion In this study, normal development before seizure onset, seizures beginning before age of one year and psychomotor retardation after age of two years are the most significant criteria in SCN1A mutation positive patients. References Dravet C, Bureau M, Oguni H, Fukuyama Y, Cokar O.Severe myoclonic epilepsy in infancy (Dravet syndrome). In: Roger J, Bureau M, Dravet C, Genton P, Tassinari CA, Wolf P, eds. Epileptic Syndromes in Infancy, Childhood and Adolescence, 4th ed. London: John Libbey Eurotext Publishers; 2005. p. 89-113. Dalla Bernardina B, Colamaria V, Capovilla G, Bondavalli S. Nosological classification of epilepsies in the first three years years of life. Prog Clin Biol Res 1983;124:165-83. Commission on Classification and Terminology of the International League against Epilepsy. Proposal for revised classification of epilepsies and epileptic syndromes. Epilepsia 1989;30:389-99. Scheffer IE, Zhang. YH, Jansen FE, Dibbens L. Dravet syndrome or genetic (generalized) epilepsy with febrile seizures plus? Brain Dev 2009;31(5):394-400. Singh R, Andermann E, Whitehouse WP, Harvey AS, Keene DL, Seni MH, et al. severe myoclonic epilepsy of infancy: extended spectrum of GEFS+? Epilepsia 2001;42(7):837-44. Scheffer IE, Harkin LA, Dibbens LM, Mulley JC, Berkovic SF. Neonatal epilepsy syndromes and generalized epilepsy with febrile seizures plus (GEFS+). Epilepsia 2005;46 Suppl 10:41-7. Harkin LA, McMahon JM, Iona X, Dibbens L, Pelekanos JT, Zuberi SM, et al. The spectrum of SCN1A-related infantile enceptic encephalopathies. Brain 2007;130(Pt 3):843-52. Sun H, Zhang Y, Liang J, Liu X, Ma X, Qin, et al. Seven novel SCN1A mutations in Chinese patients with severe myoclonic epilepsy of infancy. Epilepsia 2008;49:1104-7. Miller SA, Dykes DD, polesky HF. A simple salting out procedure for extracting DNA from human cucleated Nucleated cells. Nucleic Acids Res 1988;16(3):2115. Marini C, Scheffer IE, Nabbout R, Mei D, Cox K, Dibbens LM, et al. SCN1A duplications and deletions detected in dravet syndrome: implications for molecular diagnosis. Epilepsia 2009; 50(7):1670-8. Striano P, Mancardi MM, Biancheri R, Madia F, Gennaro E, Paravidino R, et al. Brain MRI findings in severe myoclonic epilepsy in infancy and genotype- correlations. Epilepsia 2007;48(6):1092-6. Wang JW, Kurahashi H, Ishii A, Kojima T, Ohfu M, Inoue T, et al. Micro chromosomal deletions involving SCN1A and adjacent genes in severe myoclonic epilepsy in infancy. Epilepsia 2008;49(9):1528-34. Lossin C. A catalog of SCN1A variants. Brain Dev 2009;31:114-30. Fountain-Capal JK, Holland KD, Gilbert DL, Hallinan BE When should clinicians order genetic testing for Dravet syndrome? Pediatr Neurol 2011;45(5): 319-23. Hattori J, Ouchida M, Ono J, Miyake S, Maniwa S, Mimaki N, et al. A screening test for the prediction of Dravet syndrome before one year of age. Epilepsia 2008;49(4):626–33. Nabbout R, Gennaro E, Dalla Bernardina B, Dulac O, Madia F, Bertini E, et al. spectrum of SCN1A mutations severe myoclonic epilepsy of infancy. Neurology 2003;60(12):1961-7. Ohmori I, Ouchida M, Ohtsuka, Y oka E, Shimizu K. Significant correlation of The SCN1A mutations and severe myoclonic epilepsy in infancy. Biochem Biophys Res Commun 2002;295:17-23. Cales. L, Del-favero J, Ceulemans B, Lagae L, Van Broeckhoven C, De jonghe P. De novo mutations in the sodium- chnnel gene SCN1A cause severe myoclonic epilepsy of infancy. Am J Hum Genet 2001; 68(8):1327-32. Brunklaus A, Ellis R, Reavey E, Forbes GH, Zuberi SM.Prognostic, clinical and demographic features in SCN1A mutation-positive Dravet syndrome. Brain 2012;135(Pt 8):2329-36. Engel J Jr; International League Against Epilepsy (ILAE).A proposed diagnostic scheme for people with epileptic seizures and with epilepsy: report of the ILAE Task force on Classifications and Terminology. Epilepsia 2001;42(6):796-803. Fujiwara T, Sugawara T, Mazaki-Miyazaki E, Takahashi Y, Fukushima K, Watanabe M, et al. Mutations of sodium channel alpha subunit type 1 (SCN1A) in intractable childhood epilepsies with frequent generalized tonic- clonic seizures. Brain 2003;126:(Pt 3):531-46. Claes L, Ceulemans B, Audenaert D, Smets K, Löfgren A, Del-Favero J. De novo SCN1A mutations are a major cause of severe myoclonic epilepsy of infancy. Hum Mutat 2003;21(6):615-21. Lakhan R, Kumari R, Misra UK, Kalita J, Pradhan S, Mittal B. Differential role of sodium channels SCN1A and SCN2A gene polymorphisms with epilepsy and multiple drug resistance in the north Indian population. Br J Clin Pharmacol 2009;68(2):214-20.